2010
DOI: 10.1055/s-0029-1246180
|View full text |Cite
|
Sign up to set email alerts
|

Führungsverhalten und Gesundheit - Zum Stand der Forschung

Abstract: The link between leaders' behaviour and health has only recently been the focus of scientific research and the results which already exist on this topic have, to date, not been systematically evaluated or summarized. The objective of this article is to make an attempt to provide a summarised overview of the current state of research. Subject-related databases list 42 publications dealing with the relationship between leaders' behaviour and the state of health and well-being of their employees. The literature d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 24 publications
3
36
0
16
Order By: Relevance
“…According to a current research with the COPSOQ dataset, the quality of leadership contributed significantly to job satisfaction [30]. Gregersen et al found in their review the first empirical evidence on the influence of various leadership style on the health of employees [31]. However, more research is needed on this aspect in the dialysis setting.…”
Section: Discussionmentioning
confidence: 99%
“…According to a current research with the COPSOQ dataset, the quality of leadership contributed significantly to job satisfaction [30]. Gregersen et al found in their review the first empirical evidence on the influence of various leadership style on the health of employees [31]. However, more research is needed on this aspect in the dialysis setting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews have reported statistically significant associations between leadership styles, stress, burnout, well-being, self-evaluation, and overall satisfaction (Gregersen et al 2011;Kuoppala et al 2008;Nyberg et al 2005;Schyns and Schilling 2013;Skakon et al 2010). Moreover, a large-scale cohort study reported statistically significant associations between supervisor behaviour and ischemic heart disease (Nyberg et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Many organizations currently have very long and/or irregular shifts, which have significant effects on workers' physical and mental health (Amelsvoort, 2004), an issue that has been linked to burnout in some relevant studies Honkonen et al, 2006;Gregersen, Kuhnert, Zimber & Nienhaus, 2010). This condition is especially important to consider in health workers, a group particularly vulnerable to suffering disorders derived from these conditions (Berger & Hobbs, 2006;Olson, Drage & Auger, 2009;Rauchenzauner, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%